2021
DOI: 10.20885/jca.vol3.iss2.art3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of company size, institutional ownership, profitability and leverage on dividends payout ratio

Abstract: The implication of this research is that company managers are expected to make dividend payout ratio decisions by looking at the factors that influence it, this is hoped that the company can avoid agency problems that can cause agency costs in the company, for corporate investors it is expected to be used as reference material for investing in the company by looking at the factors that affect the dividend payout ratio before investing, this study is expected to provide information about the factors that can af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 7 publications
(14 reference statements)
1
8
0
Order By: Relevance
“…Armenia et al (2021) found that there is a causality relationship between delta and vega. By applying the simulation approach, the portfolio of the CEOs consisting of delta and vega asserts the increasing trend in the case of a riskier firm.…”
Section: Ceo Compensation and Capital Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Armenia et al (2021) found that there is a causality relationship between delta and vega. By applying the simulation approach, the portfolio of the CEOs consisting of delta and vega asserts the increasing trend in the case of a riskier firm.…”
Section: Ceo Compensation and Capital Structurementioning
confidence: 99%
“…Waris et al ( 2021 ) also found the same results related to governance and payout using control variables such as size, growth, and profitably. According to Widodo et al ( 2021 ) within the presence of the restriction imposed by the company on outsourcing financing, the payout ratios of such types of companies are lower. The firm owner participation in the board of directors enhances the dividend payout.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Management becomes aware of a repeated cycle between dividends and the firm's value (John & Williams, 1985). Directors of a firm will possibly announce dividends but in fact, dividends are often used as an indicator to develop a firm's future funding (Widodo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…23969/jrak.v15i2.6585 In determining the number of dividends, shareholders are engaged with the number of shares they own. Shareholders wanted a seamless predictable distribution because the consistency of dividends could boost selfconfidence in business (Widodo et al, 2021). Easy money came with high risk, which was why shareholders needed to learn about a company vigorously to check and make a strategy.…”
Section: Introductionmentioning
confidence: 99%